Front Cover: Revealing the Inhibitory Effect of Ginseng on Mitochondrial Respiration through Synaptosomal Proteomics. Issue 11 (17th June 2018) - Kong, Dezhi; Tian, Xiaolin; Li, Yunshan; Zhang, Saihang; Cheng, Yiru; Huo, Lifang; Ma, Huanhuan; Yang, Zuxiao; Ren, Leiming; Zhang, Mingquan; Zhang, Wei
Abstract : DOI:10.1002/pmic.201700354 Protective effects of ginseng on neurological disorders were reported by many literatures. In article number1700354, Kong et al. aim to identify global protein expression changes within cerebral cortical and hippocampal tissues when ginseng was administrated using large scale synaptosomal proteomics studies. The results indicate the majority of the altered proteins to be located in the mitochondria, directly or indirectly inhibiting mitochondrial oxidative respiration. Functional experiments confirm that ginseng's active ingredients—ginsenosides are able to inhibit oxidative phosphorylation in mitochondria.